MEMBANGUN KEBERLANJUTAN LINGKUNGAN MELALUI INOVASI SOSIAL MEKARSARI PROGRAM CSR PT INDONESIA POWER UBP GRATI DI DESA RANUKLINDUNGAN, PASURUAN - Hasani, Mj Rizqon; Khayubi, Akhmad; Asmadi, Muhammad; Adhi, Bangkit Kresna (Jurnal Abdi Insani, 2024)
The MEKARSARI program (from acronym in Bahasa Indonesia for Sustainable Model for Waste Management and Ranu Grati Empowerment) is a social initiative launched by PT INDONESIA POWER UBP GRATI in Desa Ranuklindungan, Grati District, Pasuruan Regency. The program was developed in response to serious environmental pollution caused by inadequate organic waste management, which has negatively impacted the ecosystem of Lake Ranu. In addition, the local fishery sector has struggled with high costs of commercial fish feed and poor water quality in fish cages due to the lack of aeration technology. The program aimed to address the dual challenge of poor organic waste management and support the local fishery sector by integrating Black Soldier Fly (BSF) maggot bioconversion technology and renewable energy, particularly solar-powered systems. The approach involved needs assessment, community training in waste management, maggot-based fish feed production, and the use of renewable energy. Technology such as waste shredders and solar-powered aeration systems was implemented as part of the program. Monitoring and evaluation were conducted to measure the environmental and economic impacts. The program successfully reduced 8.9 tons of organic waste annually, corresponding to a reduction in CO₂ emissions by 8.9 tons per year. Additionally, farmers saved approximately IDR 300,000 per day through the production of maggot-based feed instead of relying on expensive commercial alternatives. Social participation also improved, and the initiative promoted a circular economy model. MEKARSARI emerged as an innovative solution that integrates waste management, fish feed production, and renewable energy, offering significant economic, social, and environmental benefits..